Sociālpedagoģiskā darbība Līvbērzes pamatskolas 6. un 7. klasēs mobinga mazināšanā, izmantojot neformālas izglītības metodes - Ostrovska, Katrīna (Latvijas Universitāte, 2021)
Diplomdarba “Sociālpedagoģiskā darbība Līvbērzes pamatskolas 6. un 7. klasēs mobinga mazināšanā, izmantojot neformālas izglītības metodes” mērķis ir raksturot mobingu, izstrādāt, un aprobēt sociālpedagoģisko programmu mobinga mazināšanā Līvbērzes pamatskolā 6. un 7. klasēs, izmantojot neformālas izglītības metodes. Teorētiskajā daļā autore sniedz mobinga vispārēju raksturojumu, mobinga izpausmes un mobinga mazināšanas iespējas izglītības iestādē un neformālas izglītības metožu raksturojumu un iespējām ar to palīdzību mazināt mobinga izpausmes skolā. Praktiskajā daļā tika veikts pētījums Līvbērzes pamatskolā 6. un 7. klasēs. Autore izstrādāja un realizēja sociālpedagoģisko programmu “Sociālpedagoģiskā darbība mobinga mazināšanā Līvbērzes pamatskolas 6. un 7. klasēs, izmantojot neformālas izglītības metodes”. Atslēgvārdi: mobings, sociālpedagoģiskā darbība, skolēni, izglītības iestāde, vardarbība, neformālā izglītība, sadarbība, projekts.

The aim of the thesis “Socio-pedagogical activity in Livberze Primary School in 6th and 7th grades in reducing mobbing using non-formal education methods” is to describe mobbing, develop and practically test a socio-pedagogical program for reducing mobbing in Livberze Primary School in 6th and 7th grades using non-formal education methods. In the theoretical part, the author provides a general description of mobbing, the manifestations of mobbing and the possibilities of reducing mobbing in an educational institution, and the description of non-formal education methods and the possibilities to reduce mobbing manifestations in school. In the practical part, research was performed in Livberze Primary School in the 6th and 7th grades. The author developed and implemented the socio-pedagogical program “Socio-pedagogical activity in reducing mobbing in the 6th and 7th grades of Livberze Primary School, by using non-formal education methods”. Keywords: mobbing, social pedagogical activity, students, educational institution, violence, non-formal education, collaboration, project.
Socio-pedagogical Activity in Livberze Primary School in 6th and 7th Grades in Reducing Mobbing using non-formal Education Methods
Keywords: Pedagoģija; mobings; sociālpedagoģiskā darbība; skolēni; izglītības iestāde; neformālā izglītība